2017
DOI: 10.1039/c7tc01594a
|View full text |Cite
|
Sign up to set email alerts
|

Carbazolylphosphines and carbazolylphosphine oxides: facilely synthesized host materials with tunable mobilities and high triplet energy levels for blue phosphorescent OLEDs

Abstract: Selectively modulating the charge mobility of host materials by the oxidation of phosphines for highly efficient blue phosphorescent OLEDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…No shift in the absorption maxima concerning P O, P S, and P Se units indicated that the electronic communication between the phenothiazine and P = X unit is negligible in the ground state. This observation parallels the UV-Vis spectra of tris-carbazole phosphoramides reported by Huang et al 95,98 The absorption process in TPTZPO, TPTZPS, and TPTZPSe is insensitive to the solvent polarity indicating the nonpolar electronic ground state in these compounds.…”
Section: Resultssupporting
confidence: 89%
“…No shift in the absorption maxima concerning P O, P S, and P Se units indicated that the electronic communication between the phenothiazine and P = X unit is negligible in the ground state. This observation parallels the UV-Vis spectra of tris-carbazole phosphoramides reported by Huang et al 95,98 The absorption process in TPTZPO, TPTZPS, and TPTZPSe is insensitive to the solvent polarity indicating the nonpolar electronic ground state in these compounds.…”
Section: Resultssupporting
confidence: 89%
“…[ 61 ] As known, the overall PCE ( η ) is one of the most quantitative parameters that describe the DSSC performance, which is directly related to the open‐circuit voltage, V oc ; short‐circuit current density, J sc ; and FF . It can be expressed as follows [ 63,64 ] : PCE()η=PmaxPin=Voc0.25emJscPinitalicFF where P max is the maximum power of the DSSC devices, and P in (=100 mW cm −2 ) is the incident solar power on the cell. The ν oc , FF , J sc , and PCE values for all studied dyes are summarized in Table 9.…”
Section: Resultsmentioning
confidence: 99%
“…Aryl phosphine oxide (APO, Scheme 1 ), with moderated electron-withdrawing ability and excellent charge transport properties, has been widely applied in blue bipolar hosts [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. Through simply replacing the O atom of APO with the S atom, aryl phosphine sulfide (APS, Scheme 1 ) can be gained.…”
Section: Introductionmentioning
confidence: 99%